FEATURES OF THE MODERN TEACHING IN SCHOOLS - Narzieva Maftuna Shuhrat qizi (Scholar Express Journals, 2021)
The teaching of subjects in modern schools is undergoing drastic changes. The classic triad of a teacher's goals for the first-come out educational and socializing purposes. And the subject content itself, having given up the target function to methods of action, gets a new role-a means of launching and maintaining the processes of self-development and self-knowledge of the student. The solution to this problem is possible thanks to the use of innovative training technologies. The term " Innovation "(innovation) is interpreted as an antonym of the adjective" Traditional", which implies going beyond the typical, most common sets of methods, methods, and techniques of training.
Keywords: Classical triad, innovative technologies, project technologies, interactive technologies, information technologies, presentations, communication technologies